Mediation of Green Purchase Behavior in the Influence of Product Quality and Environmental Knowledge on Green Consumer Satisfaction in Agribusiness Marketing - Taufiq Hidayat (ASA : Agribusiness and Sustainable Agriculture, 2026)
This study examines how product quality and environmental knowledge shape green purchase behavior and subsequently impact green consumer satisfaction within the context of digital marketing for environmentally friendly agricultural products in Indonesia. Despite growing environmental awareness, this awareness does not always translate into green purchasing decisions. Doubts about the quality of green products and limited consumer knowledge often influence purchasing choices and post-consumption satisfaction. The novelty of this study lies in the integration of pre-purchase factors, purchase behavior, and consumer satisfaction within the context of green agricultural products marketed through digital platforms, a domain still rarely explored in developing countries. A quantitative approach was employed, surveying 350 young digital consumers. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to evaluate direct and mediating effects. Product quality and environmental knowledge positively influence green purchase behavior, which mediates and strengthens green consumer satisfaction. Enhancing product credibility and environmental literacy is crucial to promoting sustainable consumption and accelerating the adoption of the green market in Indonesia.